2020
DOI: 10.5765/jkacap.200020
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Emotional Empathy in Young Adolescents: an fMRI Study

Abstract: Objectives: We investigated the differences in cognitive and emotional empathic ability between adolescents and adults, and the differences of the brain activation during cognitive and emotional empathy tasks. Methods: Adolescents (aged 13-15 years, n=14) and adults (aged 19-29 years, n=17) completed a range of empathic ability questionnaires and were scanned functional magnetic resonance imaging (fMRI) during both cognitive and emotional empathy task. Differences in empathic ability and brain activation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…Likewise, one study reported stronger activation in the right superior, middle, and inferior frontal cortices in adults when performing tasks associated with cognitive empathy and theory of mind (ToM) [90], whilst another study found increased activity in the right middle frontal during cognitive perception of emotional pain [91]. Collectively, these findings suggest a disturbance in the salience and default mode networks in our sample, which are activated during the selection and monitoring of salient emotional stimuli and the perception of self and other emotional state, respectively [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, one study reported stronger activation in the right superior, middle, and inferior frontal cortices in adults when performing tasks associated with cognitive empathy and theory of mind (ToM) [90], whilst another study found increased activity in the right middle frontal during cognitive perception of emotional pain [91]. Collectively, these findings suggest a disturbance in the salience and default mode networks in our sample, which are activated during the selection and monitoring of salient emotional stimuli and the perception of self and other emotional state, respectively [3].…”
Section: Discussionmentioning
confidence: 99%
“…The right cingulate cortex and insula have been implicated in emotion contagion and emotional empathy [89]. Furthermore, some functional neuroimaging studies have demonstrated the prefrontal cortex, frontal pole, and temporal regions in mediating complex cognitive function, including PT and mentalisation [5,90,91]. Multani et al [5] found a loss of cognitive empathy and emotional detection deficit in AD, bvFTD, and PD that were related to decreased functional connectivity mainly in the right inferior temporal gyrus, frontal pole, paracingulate gyrus, insular, and inferior parietal lobule.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that physical neglect is negatively related to the morphology indices of the transverse temporal cortex, superior parietal lobule, and insula. These regions play important roles in sensory, affective, and attention reactions, as well as in cognitive processing (71). Therefore, we found that a failure to meet the physical needs of children could affect brain areas mainly involved in attention, reward, and sensorimotor processing, as well as affective and social cognitive abilities.…”
Section: Associations Of Physical Neglect With Brain Abnormalities Related To Widespread Functionsmentioning
confidence: 93%
“…Other studies show that as children develop, there are changes in which regions are used for cognitive and affective empathy as well as how strongly they are activated. In brief, younger-aged people use a more bottom-up response to an emotionally charged situation, and as they age, a more top-down approach is utilized as the cerebral cortex, especially the prefrontal cortex, matures after the teenage years [64,65]. In a chapter by Newton [44], studies are reviewed that show how physicians empathically respond to noncompliant patients and to patients who are disparate from themselves.…”
Section: Varied Other Factors Can Influence Empathymentioning
confidence: 99%